The International Labour Organisation in pursuit of decent work in Southern Africa: An appraisal - Mokofe, William Manga (Obiter, 2020)
This article examines the role of the International Labour Organisation (ILO), regional standards, and the “decent work agenda” in addressing challenges facing non-standard workers in southern Africa. Employees in traditional full-time employment are well protected in some southern African states, but the regulation currently available is largely unable to protect non-standard workers, and in numerous instances workers are regarded as “non-standard”, on the basis of a narrow interpretation of the term “employee”. Casualisation and externalisation have resulted in the exclusion of numerous workers from the protection provided by labour legislation, and union cover for non-standard workers is very low. The article further discusses the relationship between non-standard employment and labour migration in southern Africa. Light is also shed on regional standards, the challenges of unemployment, poverty, and income inequality, and labour-market transitions in southern Africa.